Pathways for Germany's Low-Carbon Energy Transformation Towards 2050 - Hans-Karl Bartholdsen; Anna Eidens; Konstantin Löffler; Frederik Seehaus; Felix Wejda; Thorsten Burandt; Pao-Yu Oei; Claudia Kemfert; Christian von Hirschhausen (Energies, 2019)
Like many other countries, Germany has defined goals to reduce its CO2-emissions following the Paris Agreement of the 21st Conference of the Parties (COP). The first successes in decarbonizing the electricity sector were already achieved under the German Energiewende. However, further steps in this direction, also concerning the heat and transport sectors, have stalled. This paper describes three possible pathways for the transformation of the German energy system until 2050. The scenarios take into account current climate politics on a global, European, and German level and also include different demand projections, technological trends and resource prices. The model includes the sectors power, heat, and transportation and works on a Federal State level. For the analysis, the linear cost-optimizing Global Energy System Model (GENeSYS-MOD) is used to calculate the cost-efficient paths and technology mixes. We find that a reduction of CO2 of more than 80% in the less ambitious scenario can be welfare enhancing compared to a scenario without any climate mitigating policies. Even higher decarbonization rates of 95% are feasible and needed to comply with international climate targets, yet related to high effort in transforming the subsector of process heat. The different pathways depicted in this paper render chances and risks of transforming the German energy system under various external influences.
Keywords: 330; Decarbonization; Energy system modeling; GENeSYS-MOD; Renewables; Energy policy; Energy transformation; Energiewende